GLUT1 is an AR target contributing to tumor growth and glycolysis in castration-resistant and enzalutamide-resistant prostate cancers. (10th August 2020) - Wang, Jun; Xu, Wenhao; Wang, Beihe; Lin, Guowen; Wei, Yu; Abudurexiti, Mierxiati; Zhu, Wenkai; Liu, Chang; Qin, Xiaojian; Dai, Bo; Wan, Fangning; Zhang, Hailiang; et al.
Abstract: Castration-resistant prostate cancer (CRPC) displays a higher 18 F-FDG PET SUVmax than hormone-sensitive prostate cancer, which suggests a greater need for glucose metabolism in CRPC. Targeting glucose metabolism in cancer cells remains attractive for cancer treatment. Glucose transporters (GLUTs) meditate the first and rate-limiting step of glucose metabolism. Here, we investigated the key mediator of glucose transporters and evaluated its therapeutic value in a preclinical model of CRPC. 18 F-FDG PET showed a higher SUVmax in CRPC than in hormone-sensitive prostate cancer, and GLUT1 expression positively correlated with SUVmax and was associated with a worse CRPC outcome. GLUT1 inhibition significantly suppressed cell growth, glycolysis and tumor volume in a xenograft model both in CRPC and enzalutamide-resistant prostate cancer. Chromatin immunoprecipitation and dual luciferase reporter assay showed that androgen receptor (AR) directly bound to the GLUT1 gene promoter to promote GLUT1 transcription. Combining GLUT1 inhibition and enzalutamide remarkably suppressed proliferation and glycolysis and induced apoptosis in CRPC cells. Our results suggest that GLUT1 is an AR target and displays synergistic effects with enzalutamide. GLUT1 may act as a promising therapeutic target in CRPC and enzalutamide-resistant prostate cancer. Highlights: GLUT1 plays a key role in regulation of 18 F FDG PET SUVmax and glucose metabolism in CRPC. GLUT1 Inhibition suppresses cell growth, glycolysis and tumor volume in CRPC and enzalutamide-resistant prostate cancer. GLUT1 is a direct target of AR, and GLUT1 inhibition displays synergistic anti-tumor effect with enzalutamide.